2020
DOI: 10.1177/1758998320948538
|View full text |Cite
|
Sign up to set email alerts
|

Translating the Strengthening and Stretching for Rheumatoid Arthritis of the Hand Programme from clinical trial to clinical practice: An effectiveness–implementation study

Abstract: Introduction The Strengthening and Stretching for Rheumatoid Arthritis of the Hand programme is a hand exercise programme for people with rheumatoid arthritis. It was clinically effective when delivered during a clinical trial but there was a need to evaluate translation into routine care. Methods We conducted an effectiveness–implementation study. We adapted the trial training into an online format for National Health Service hand therapists. Educational outcomes included confidence and capability to deliver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…We have used this approach previously. 114,115 The online training addresses implementation barriers as well as providing the content needed for successful implementation.…”
Section: Implementation Is Guided By the I-parihs (Integrated Promoti...mentioning
confidence: 99%
“…We have used this approach previously. 114,115 The online training addresses implementation barriers as well as providing the content needed for successful implementation.…”
Section: Implementation Is Guided By the I-parihs (Integrated Promoti...mentioning
confidence: 99%
“…The Strengthening and Stretching for Rheumatoid Arthritis of the Hand (SARAH) trial showed that a tailored strengthening and stretching hand exercise program in addition to usual care led to improvements in hand function at 12 months and was considered to be both clinically and cost effective [ 59 ]. The original intervention [ 59 ] was six sessions of face-to-face contact with a physiotherapist or occupational therapist, but when implemented into a clinical setting the majority of therapists delivered only four sessions, often omitting behavioural strategies designed to support physical activity adherence [ 60 ]. However, the researchers anticipated potential implementation barriers and put strategies to overcome these in place.…”
Section: Exercise Implementation In Iamentioning
confidence: 99%
“…However, the researchers anticipated potential implementation barriers and put strategies to overcome these in place. For example, in the SARAH program, face-to-face training for therapists was considered unfeasible when translating the program to nationwide delivery and the training was successfully moved to an online platform [ 60 ]. While intervention flexibility of delivery may be beneficial (by improving uptake), assessment of the impact of intervention changes is important, as when adaptations of interventions move away from the evidenced trial protocol, they may be less effective than the original trial.…”
Section: Exercise Implementation In Iamentioning
confidence: 99%
See 1 more Smart Citation